Faktor Yang Mempengaruhi Kepatuhan Wajib Pajak Di Kpp Pratama Jakarta Palmerah - Michelle Marceline, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research aims to determine the effect of taxpayers awareness, taxation knowledge, and tax penalties on the compliance of individual taxpayers at KPP Pratama Jakarta Palmerah. This research uses primary data which the method to get the data by distributing questionnaires to individual taxpayers at KPP Pratama Jakarta Palmerah. The distribution of questionnaires was conducted on 22nd-24th October 2018. The samples used in this study is 110 respondents. The results showed that the taxpayers awareness did not have a positive effect on the compliance of individual taxpayers in KPP Pratama Jakarta Palmerah, while taxation knowledge and tax penalties had a positive effect on the compliance of individual taxpayers at KPP Pratama Jakarta Palmerah.